A dual signal amplification method for miR-204 assay by combining chimeric molecular beacon with double-stranded nuclease. Issue 48 (4th December 2018) - Liu, Hao; Fan, Jialong; Liu, Weiping; Tong, Chunyi; Xie, Zhenhua; Deng, Rilin; Long, Xiaoyan
Abstract : Due to the miRNA's key roles in early disease diagnosis, an assay based on chimeric molecular beacon was constructed for miR204 detection with LOD lower to 50 pM. Abstract : Identifying microRNAs (miRNA) as biomarkers has attracted much attention owing to their key roles in early disease diagnosis and assessing the prognosis and monitoring the outcome of therapy. However, the rapid and efficient detection of microRNA levels remains challenging. By combining the specificity targeting of chimeric molecular beacons with the signal amplification ability of double-stranded nuclease, we now report a rapid, sensitive, and selective miRNA204 assay. This assay can detect miR-204 at concentrations as low as 50 pM with a linear range of 50 pM to 10 nM. This method also shows the ability to discriminate target sequences containing mismatched bases. This could be a promising tool for selective analysis of miRNAs in vitro .